Assessment of Vitamin B12 Deficiency and Associated Factors in Patients Attending Tertiary Care Hospital of Southern Rajasthan - Poornima Sharma; Keerti Singh; Rekha Bhatnagar; Rohit Jain (Medsci Publications, 2018)
Introduction: Vitamin B12 deficiency is gaining increasing im- portance as a public health issue as subclinical deficiency is report- ed to exist in India in more than 30% of adults and children. Thus the present study was done to find the burden of vitamin B12 defi- ciency in the symptomatic patients in the tertiary care centre and to analyze its association with demographic profile, dietary habits and severity of presenting symptoms. Method: A 3 months long cross-sectional study was done in 235 symptomatic patients who were biochemically tested for serum Vitamin B12 levels. Results: Almost 25.1% patients with symptoms were found defi- cient in Vitamin B12 at the study centre. Deficiency is higher in males i.e. 29.6%. Higher deficiency levels were found in urban population i.e. 30.6% and vegetarians (27.7%). Maximum deficien- cy was seen in females when they presented with late neurological deficit like dementia or seizures (42.8%). Conclusion: Approximately 1/4th of the symptomatic population was found Vitamin B12 deficient suggesting the clinical deficiency showing the tip of the iceberg. Study findings suggest  public health issue, thus further community based studies are required to evaluate it in India with large sample size and compelling IEC ac- tivities regarding dietary habits and early reporting of the symp- toms and prompt treatment.